Traditional vs. Modern Medicine: Community Preferences and Health Anthropology in North Sulawesi - Wiyono, Weny Indayany; Lolo, Widya Astuty; Yamlean, Paulina Veronika Yolanda (Borneo Journal of Pharmacy, 2026)
This study explores community preferences and decision-making in the use of traditional and modern medicine in North Sulawesi from a health anthropology perspective. Using a qualitative descriptive approach, in-depth interviews were conducted with 15 participants, and data were analyzed thematically to identify patterns of perception and factors influencing treatment choice. The results show that traditional medicine is preferred for mild illnesses due to perceptions of safety, affordability, and cultural familiarity, whereas modern medicine is favored for severe or chronic conditions because of its clinical validation, measurable outcomes, and professional supervision. However, a growing trend of complementary use, combining both traditional and modern treatments, was observed, motivated by safety concerns, family or peer advice, and information obtained through the internet, especially social media. The study concludes that decision-making in the use of traditional and modern medicine in North Sulawesi is influenced by illness severity, perceptions, social factors, and access to information. Traditional medicine is preferred for mild conditions, whereas modern medicine is used for severe or chronic illnesses. The combined use of both reflects a pragmatic approach within a pluralistic health system. These findings highlight the need for culturally grounded integration and improved health literacy.